Simbol Dalam Pelaminan Adat Banjar Pada Etnis Banjar Kuala Di Desa Tinggiran II Luar Kecamatan Tamban Kabupaten Barito Kuala - Latifah Latifah; Laila Azkia (Universitas Lambung Mangkurat, 2024)
A symbol is an interaction used by humans, where the symbol has a meaning. This research aims to (1) Find out what symbols are contained in the traditional banjar wedding altar for the Banjar Kuala ethnic group in Tinggiran II Luar Village (2) Find the meaning contained in the traditional banjar wedding symbol for the Banjar Kuala ethnic group in Tinggiran II Luar Village. The method used in this research is a qualitative research method. Data sources were selected using snowball and purposive sampling. Data collection was carried out using observation, interviews and documentation techniques. The data analysis techniques used are data reduction techniques, data presentation and conclusion drawing. Testing the validity of the data was carried out by source triangulation, technical triangulation and time triangulation. The results of the research show that: (1) There are six symbols found on the traditional banjar altar of the Banjar Kuala ethnic group in Tinggiran II Luar Village, namely: (a) jasmine flowers, (b) sarai flowers, (c) curtains, (d) cushions , (e) colors on the Banjar traditional wedding, (f) pidasar. (2) The meaning contained in the traditional banjar wedding symbol for the Banjar Kuala ethnic group in Tinggiran II Luar Village is: (a) perfection of the wedding ceremony, (b) safety and protection, (c) remembering and respecting ancestors.